eIF4A controls translation of estrogen receptor alpha and is a therapeutic target in advanced breast cancer - Jacob A. Boyer; Ezra Y. Rosen; Malvika Sharma; Madeline A. Dorso; Nicholas Mai; Corina Amor; Jason M. Reiter; Ram Kannan; Sunyana Gadal; Jianing Xu; Matthew Miele; Zhuoning Li; et al. (Proceedings of the National Academy of Sciences, 2025)
Most breast cancers depend on hormone-stimulated estrogen receptor alpha (ER) activity and are sensitive to ER inhibition. Resistance can arise from activating mutations in the gene encoding ER ( ESR1 ) or from reactivation of downstream targets. Newer ER antagonists occasionally show efficacy but are largely ineffective as single agents in the long term. Here, we show that ER translation is eIF4E/cap-independent yet sensitive to inhibitors of the translation initiation factor eIF4A. EIF4A inhibition reduces the expression of ER and cell cycle regulators such as cyclin D1. This leads to growth suppression in ligand-independent breast cancer models, including those driven by ER mutants and fusion proteins. Efficacy is enhanced by adding the ER degrader, fulvestrant. The combination further lowers ER expression and blocks tumor growth in vitro and in vivo. In an early clinical trial (NCT04092673), the eIF4A inhibitor zotatifin was combined with either fulvestrant or fulvestrant plus CDK4 inhibitor, abemaciclib, in patients with acquired resistance to these agents. Multiple clinical responses including a handful of durable regressions were observed, with little toxicity. Thus, eIF4A inhibition could be useful for treating ER+ breast cancer resistant to other modalities.